Teknologi dan produktivitas: manfaat dan dampak yang disebabkan - Rhamdhani, Alfiyati Alfiyati (Maliki Interdisciplinary Journal, 2025)
In the digital era like now, technology has a very influential impact on every productivity. Technological developments also always develop more rapidly every day. The use of technology in various activities has provided various impacts, such as positive impacts and negative impacts. Using technology for daily productivity can help work processes become more effective and efficient. This will be discussed in more detail later in this article. The main benefits of technology on productivity are shortening time, increasing work productivity and so on. Apart from the benefits, there are also impacts from technology, while another impact of benefits is dependence on use. Because in an era like today, both children and toddlers to adults are never separated from the word gadget.